Leucopaxillus pakistanicus, a new species of (Tricholomataceae: Basidiomycota) from the coniferous forest of Pakistan - Khan, Rameez; Ullah, Shariat; Khalid, Abdul Nasir (Phytotaxa, 2024)
Leucopaxillus pakistanicus sp. nov. is described and illustrated from Upper Dir, Khyber Pakhtunkhwa, Pakistan, based on a comprehensive description of morphology and phylogeny. Leucopaxillus pakistanicus is characterized by brick red or red-brown, slightly thin fleshed, creamy short and decurrent thick lamellae, long, slender and fistulose stipe, glutulated and thick-walled basidiospores and subcapitate cheilocystidia. Phylogenetically, this is a distinct species although closely related to Leucopaxillus amarus, Leucopaxillus laterarius and Leucopaxillus gentianeus.